About elder mistreatment: a brief report - Henna Fatma; Soomal Rafique; Saira Furqan (Geriatric Care, 2022)
Elder mistreatment, initially coined as ‘Granny Battering’ in 1975 by British gerontologists is an issue that has seldom received any attention in our part of the world, mostly due to lack-luster reporting. With tertiary care setups in low to middle income countries administering care to a burgeoning population of elderly patients, elder abuse has now become increasingly apparent. This case report examines elder mistreatment in a drowsy patient living with her son, who had recently appointed a private nurse for her care. Our healthcare team proceeded to provide the best available medical and community resources in the care and intervention of the patient.